A Chat Among Friends: In Conversation with Siegfried Gerhardt - Broccaioli Masiero, Franca (Oltreoceano - Rivista sulle migrazioni, 2024)
We can become exiles for a number of diverse reasons; among them, there is the need to find work or flee from a totalitarian regime where freedom of thought is considered a crime. Siegfried Gerhardt’s experience as an expatriate for the latter reason bears witness to the deep bitterness that exiles feel when they end up in hostile places and with people who do not interact with them thus making them feel as intruders and hindering their integration and re-appropriation of identity. This feeling is even more painful in Gerhardt’s case since he considers himself as “an exile from his homeland” ‒ a statement which echoes a famous phrase by the well-known poet and writer Adelbert von Chamisso who spent his whole life painfully wandering as an exiled person: I am always out of place; I never feel in the right place. It is thus necessary to “exile oneself from exile”, to find strength and consolation in the beauty (and goodness) of art ‒ Dostoevskij’s eternal idea that saves us from the hostilities of life. This is what Siegfried Gerhardt has done.